Appropriate Surrogate Endpoint in Drug-Coated Balloon Trials for Coronary Artery Diseases - Lang, Xinyue; Wang, Yang; Li, Wei; Liu, Xiaoyun; Zhao, Yanyan; Wang, Chuangshi; Li, Xiaocong; Zhu, Yingxuan; Li, Mengya; Song, Lei; Xu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Background: The appropriateness of using late lumen loss (LLL) as a surrogate endpoint was established in drug-eluting stent (DES) studies, but it was less supportive for drug-coated balloons (DCB) trials. Methods: Studies were searched from PubMed, EMBASE, Cochrane Library and ClinicalTrials.gov until June 23, 2021. Correlation between LLL, MLD (minimal lumen diameter) or %DS (percentage diameter stenosis) and clinical endpoints was evaluated by linear regression. Standardized effect size and its 95% confidence intervals (CI) were used to illustrate the difference among LLL, MLD and %DS. Results: 24 clinical trials were eligible (16 DCB vs. DES, 7 DCB vs. plain old balloon angioplasty (POBA) and 1 DCB vs. DES vs. POBA). 13 (54.2%) trials used LLL as the primary endpoint. LLL, MLD and %DS all had significant associations with clinical endpoints. For DCB vs. DES trials, the number of studies reported inconsistent results between LLL and MLD, LLL and %DS were 12/16 (75.0%), 10/15 (66.7%), separately; while in MLD and %DS was 1/16(6.3%). The differences of standardized effect size between LLL and MLD, LLL and %DS were -0.47 (95% CI, -0.69 to -0.25, p < 0.001) and -0.31 (95%CI, -0.43 to -0.20, p < 0.001); while in MLD and %DS was not, 0.1 (95%CI, -0.02 to 0.22, p = 0.084). Conclusions: For DCB trials, an appropriate surrogate is associated with the control device. The traditional LLL could be used among the DCB vs. POBA trials. However, MLD/%DS should be considered as a more suitable surrogate endpoint when comparing DCB with DES.